Antioxidant properties and detailed polyphenol profiling of European hornbeam (Carpinus betulus L.) leaves by multiple antioxidant capacity assays and high-performance liquid chromatography/multistage electrospray mass spectrometry - Hofmann Tamás (INDUSTRIAL CROPS AND PRODUCTS, 2016)
According to recent studies, the antioxidant and anticancer related properties of European hornbeam (Carpinus betulus L.) leaf extracts are remarkable, making it a possible raw material for medicine, requiring the identification of major active compounds and the assessment of the antioxidant properties of the extracts. In the present work the high-performance liquid chromatographic/multistage mass spectrometric characterization of the antioxidant polyphenolic compounds as well as the evaluation of the seasonal changes in the major antioxidant capacity and related parameters (DPPH, ABTS, FRAP, total phenol content, total flavonoid content and total flavan-3-ol content) have been carried out for the leaves of European hornbeam for the first time. The extracts exhibited the highest antioxidant capacity in August, basing on the FRAP (106.24 ± 3.10 mg AAE/g dw.) and DPPH (IC50: 4.63 ± 0.88 μg/ml) assays and in May, based on the ABTS (329.78 ± 23.89 mg TE/g dw.) method. From the August extract a total of 171 compounds, including phenolic acids, flavonoid glycosides, tannins, catechins and procyanidins have been characterized and identified. According to the HPLC-PDA peak areas, the most abundant polyphenolic compounds in the August extracts were chlorogenic acid, ellagic acid, ellagitannins, myricetin-, luteolin-, quercetin- and apigenin glycosides. Further research is needed for the elucidation of the compounds which are primarily responsible for the antioxidant properties. © 2016 Elsevier B.V.